Social Network Typologies of Black and White Married Couples in Midlife. Issue 2 (22nd July 2016) - Fiori, Katherine L.; Rauer, Amy J.; Birditt, Kira S.; Brown, Edna; Jager, Justin; Orbuch, Terri L.
Abstract: Although research shows that conjoint social networks are associated with well‐being among newlyweds, little is known about how these network types are linked to marital quality and psychological well‐being for long‐term married couples and about potential race differences in their configurations and associations. Using a pattern‐centered approach to examine the social networks of 91 White and 62 Black couples in their 16th year of marriage, this study revealed four couple network types (friend‐focused, wife family‐focused, bilateral family‐focused, and diverse). Results suggested that spouses in the wife family‐focused network type (characterized by above‐average contact with the wife's family and below average contact with the husband's family and with nonkin) reported the lowest positive marital quality and highest negative marital quality. The association of network type with negative marital quality was also moderated by gender and race. The findings highlight the importance of considering the meaningful complexity within couples' shared networks.